A Staged Approach for Energy Retrofitting an Old Service Building: A Cost-Optimal Assessment - Jorge Lopes (MDPI AG, 2021)
Office buildings built before the pre-1960 age constitute a relevant group for analyzing the energy performance of the Portuguese building sector. A dynamic energy simulation was used to assess the energy performance of an existing office building located in the town of Bragança, Portugal. By using a staged renovation approach, two passive technologies applied to the building envelope and an efficient domestic hot water system were selected and a financial evaluation through the net saving (NS) method was undertaken to choose the best efficiency measures/packages for improving the building’s energy performance. Real discount rates of 3% and 1% were used in the financial evaluation. Considering the real discount rate of 3%, the results showed that only two out seven retrofit options had a positive financial return. By using the real discount rate of 1%, all retrofit options were found to be financially efficient. The results of the study corroborated those of earlier works that found that the financial profitability of energy renovation investments is very sensitive to the discount rate used in the analysis. The results of the study also suggested that the staged renovation approach used in the analysis is economically feasible, and that this approach is an alternative to one-step renovation approach to help to achieve the country´s energy and climate targets by 2030. Suggestions for future research conducted for office buildings in the different climate zones and other age groups in Portugal are proposed.